Die Vindiciae Contra Tyrannos en die Middeleeuse Politieke Filosofie - Raath, Andries (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2021)
According to Harold J. Berman, the Western political and intellectual tradition has been transformed in the course of its history by six great revolutions. The fifth great revolution ? according to Berman, still going backward in time ? was the Protestant Reformation, which in Germany had the character of a national revolution, starting with Luther’s attack upon the papacy in 1517. Berman adds that the sixth, the papal Revolution of 1075-1122, was also called a reformation at the time, the Reformation of Pope Gregory VII, generally translated into modern languages as the Gregorian Reform, thereby concealing still further its revolutionary character. Berman surmises that these revolutions manifested as recurrent periods of violent upheaval, in which the pre-existing system of political, legal, economic, religious, cultural, and other social relations, institutions, beliefs, values and goals has been overthrown and replaced by a new one. Although there is by no means a perfect symmetry in these periods of great historical change; yet there are certain patterns or regularities ? each one marked by fundamental, rapid, violent and lasting change in the social system as a whole; each one sought legitimacy in a fundamental law, a remote past and an apocalyptic future; each took more than one generation to establish roots, and each eventually produced a new political and intellectual system. In this article, Berman’s views on the Protestant movement representing a revolutionary epoch are considered with reference to the political theories advanced by Protestant Reformers like the author of the Vindiciae Contra Tyrannos. Three fundamental ideas undergirding the author’s political theory in the Vindiciae Contra Tyrannos are compared with the political thought of the preceding medieval epoch, viz.: 1. The notion of the supremacy of the law and the idea of public justice; 2. The impact of law and community usages on political theory; 3. The legislative authority of the ruler and the emergence of political contractarianism. It is concluded that the author of the Vindiciae Contra Tyrannos did not deviate from these classical medieval notions in the political views of the Middle Ages. In the field of political theory, Berman’s views on the revolutionary nature of Protestant political theory, therefore, have to be reconsidered.